Study The Effect of Nano-Flavonoid and Flavonoid Compounds Extraction from Bacopa Monnieri L. On The Serratia Marcescens - Al-Hassany, Maysam I. A.; J. Alwash, Bushra M. (Journal of Neonatal Surgery, 2025)
This study aimed to explore whether extract flavonoid and nano flavonoids can function as an anti-biofilm agent produced by Serratia marcescens . Firstly, flavonoid extraction from the Bacopa monnieri L. and identification by using High Performance Liquid Chromatographic (HPLC) then used casein to manufacture flavonoid-casein nanoparticles by ultrasound method . Several techniques have been used to determine the chemical and physical properties of nanoparticles such as Scanning Electron Microscope (SEM) and Zeta–Potential . S. marcescens isolates were collected and identified by culturing on Blood agar and MacConkey agar medium and confirmed by VITEK 2 system . Flavonoid and nano-flavonoids showed remarkable biofilm inhibitory effect on isolates of multidrug resistant S. marcescens . Strong biofilm producer strains show weak biofilm production After incubation for 24 hours at 37Co with MIC concentration of flavonoid and nano flavonoids